(3CSGSjGJ aj Yde bjGOI EOGQI GdbjGOIs - (3WGQb YHO GdMejO(B, (3GdHOhjs ((3YeGf(B:s (3OGQ GdacQ(B,s, 2002)
(3Yde EOGQI GdbjGOI(B-(3fXQjI GdbQGQGJ GdEOGQjI(B-(3GdbjGOI YfUQ GdJhLjgs
Keywords: (3GdbGOI GdGOGQjhfs; (3GdbjGOI GdGOGQjIs